Optimalisasi Keterampilan Membaca dan Menulis Melalui Program Beringin Aksara pada Siswa Sekolah Dasar - Paramartha, Wayan Eka; Sukadana, I Gede Wahyu (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2024)
For primary school pupils, reading and writing skills are essential, but there are still obstacles in the way of their development. To improve these abilities, this study assesses how well the interactive and captivating Beringin Aksara program works. The study included a control group that received regular teaching and an experimental group that participated in the program using a pre-post experimental design. The experimental group's mean score on the pre-test was 65 (median 68), while the control group's mean score was 62 (median 64). Post-test results showed that the experimental group had significantly improved, with a mean score of 78 (median 80) compared to 64 (median 66) for the control group. A significant difference between the groups was found by a t-test analysis (t = 5.67, p < 0.001), indicating the impact of the program.